Pojęcie lichwy w ekonomii islamskiej - Bukowski, Adam (Annales. Etyka w Życiu Gospodarczym, 2014)
The concept of Islamic economics as a coherent economic and financial system basically does not exist. Some authors take it, however, for simplicity, under-standing by this description any entities and legal regulations, mainly in the financial markets, driven – either declaratively or in fact – on the principles derived from religious precepts of Islam. The emphasis is put on so-called inter-est-free banking, which involves the concept of usury (riba).By referring to the essence of Islamic economics, the author shows the dif-ferences and similarities between "interest-free" Islamic banking and conven-tional banking (Western-style). It turns out that the differences are almost exclu-sively at the level of declarations and similarities that arise from attempts to circumvent religious regulations, as in the riba, are much more numerous than it might seem. They result from the need to fuse Islamic finances with global fi-nancial markets, which at least at the point of contact eliminates the capability of maintaining the autonomy of the local banking system. In addition, interest-free Islamic banking development meets an obstacle in the shape of the market pres-ence of conventional banks, which are its natural ideological competition. Thus, although the Islamic Development Bank estimates the size of the market of the Islamic system of financial services in 2015 at between 2 to 8 trillion dollars, one seems to be entitled to conclude that, in practice, between Islamic economics and capitalist economies of the West, at least in terms of banking services, the dif-ferences are purely semantic, and both Western and Islamic deposit, credit and investment products are in fact identical.